2012
DOI: 10.1002/marc.201200046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Selectivity for the Hydrolysis of Block Copoly(2‐oxazoline)s in Ethanol–Water Resulting in Linear Poly(ethylene imine) Copolymers

Abstract: The ability of merging the properties of poly(2-oxazoline)s and poly(ethylene imine) is of high interest for various biomedical applications, including gene delivery, biosensors, and switchable surfaces and nanoparticles. In the present research, a methodology for the controlled and selective hydrolysis of (co)poly(2-oxazoline)s is developed in an ethanol-water solvent mixture, opening the path toward a wide range of block poly(2-oxazoline-co-ethylene imine) (POx-PEI) copolymers with tunable properties. The un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
3
40
1
Order By: Relevance
“…pEI-stat-pPhOx copolymers were both, thermo-and pH-responsive. In another study, Hoogenboom et al reported that pronouncedly selective hydrolyses of poly(2-oxazoline)s could be performed in water-ethanol solutions [213]. The block copolymer pMeOx 60 -block-pPhOx 15 , for example, could be hydrolyzed such that 95% of the methyl side-chains, but only 10% of the phenyl side-chains were cleaved.…”
Section: Partial Hydrolysis: Copolymers Containing Units Of Peimentioning
confidence: 99%
“…pEI-stat-pPhOx copolymers were both, thermo-and pH-responsive. In another study, Hoogenboom et al reported that pronouncedly selective hydrolyses of poly(2-oxazoline)s could be performed in water-ethanol solutions [213]. The block copolymer pMeOx 60 -block-pPhOx 15 , for example, could be hydrolyzed such that 95% of the methyl side-chains, but only 10% of the phenyl side-chains were cleaved.…”
Section: Partial Hydrolysis: Copolymers Containing Units Of Peimentioning
confidence: 99%
“…[ 20 ] The molecular characteristics of the precursor gradient copolymers are shown in Table 1 . The rest of chemicals (EtOH and HCl 37%) were supplied by Aldrich/Fluka, and were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…After hydrolysis (reaction time 3 or 6 h), the mixture was cooled in an ice bath and neutralized with NaOH solution to a pH 8-9. [ 20 ] Copolymers were isolated by a rotor evaporator. The hydrolysis reaction is shown schematically in Scheme 1 .…”
Section: Hydrolysis Of Methyl/phenyl Oxazoline Gradient Copolymers/symentioning
confidence: 99%
See 2 more Smart Citations